2020
DOI: 10.1515/iral-2017-0118
|View full text |Cite
|
Sign up to set email alerts
|

Generating predictions based on semantic categories in a second language: A case of numeral classifiers in Japanese

Abstract: This study examined whether native Japanese speakers and second language (L2) speakers of Japanese use information from numeral classifiers to predict possible referents. Using a visual-world eye-tracking paradigm, we asked participants to identify picture objects that take either the same or different numeral classifiers while they listened to Japanese sentences referring to one object. The results showed that native speakers looked to the target predictively more often when the classifier was informative abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Similarly, Kim (2018) observed no effects of proficiency, measured through three independent tasks, on L2 learners' use of implicit causality to preactivate upcoming referents. In the domain of morphosyntax, neither Hopp (2015) nor Mitsugi (2018), focusing on case marking in L2 German and numeral classifiers in L2 Japanese respectively, found modulation of predictive effects by proficiency. Notably, both of these studies reported significant effects of proficiency on later processes of information integration, indicating that the proficiency measures employed were able to capture relevant variability between participants; yet this variability did not modulate engagement in prediction.…”
Section: Prediction Among Language Users Other Than Native-speaking College Studentsmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Kim (2018) observed no effects of proficiency, measured through three independent tasks, on L2 learners' use of implicit causality to preactivate upcoming referents. In the domain of morphosyntax, neither Hopp (2015) nor Mitsugi (2018), focusing on case marking in L2 German and numeral classifiers in L2 Japanese respectively, found modulation of predictive effects by proficiency. Notably, both of these studies reported significant effects of proficiency on later processes of information integration, indicating that the proficiency measures employed were able to capture relevant variability between participants; yet this variability did not modulate engagement in prediction.…”
Section: Prediction Among Language Users Other Than Native-speaking College Studentsmentioning
confidence: 82%
“…The null effect of proficiency may appear surprising as it is a commonly stated assumption that proficiency modulates L2 learners' engagement in predictive processing (e.g., Kaan, 2014). As discussed above, however, empirical support for this assumption has been remarkably weak, with multiple studies targeting different linguistic phenomena, in different languages, and using a variety of proficiency measures, reporting no significant effects of proficiency on predictive processing (Djikgraaf et al, 2017;Hopp, 2015;Ito et al, 2018;Kim, 2018;Mitsugi, 2018). Proficiency also did not significantly modulate L2 learners' reference and coherence choices in Grüter et al's (2017) story continuation study.…”
Section: Discussionmentioning
confidence: 96%
“…During the sentence learning task, there was no direct visual input corresponding to classifiernoun relations, and thus, classifiers may have required more time to be learned regardless of prior knowledge. In order to test these hypotheses, future research should include a control group of participants whose native language contains classifier-like rules, such as in Japanese (Mitsugi, 2018;Sudo, 2016), and compare differences in learning to participants who have no prior linguistic experience with classifier-noun rules.…”
Section: Mini Pinyin As a Valid Paradigm To Study Higher-order Languamentioning
confidence: 99%
“…Prevalent among the reported L1/L2 differences in prediction are differences in the time course of prediction. A later onset of prediction in L2 processing relative to L1 processing has been reported for the use of semantic information such as the lexicalsemantics of verbs (Chun & Kaan, 2019), the semantics of classifiers (Mitsugi, 2018), negative polarity adverbs (Mitsugi, 2022), the broader semantic context (Dijkgraaf, Hartsuiker & Duyck, 2019;, gender stereotypes (Corps, Liao & Pickering, in press), the use of morphosyntactic information such as number encoded at the verb (Koch, Bulté, Housen & Godfroid, 2021) as well as discourse-level information (Kim & Grüter, 2021). In addition to differences in the time course, several studies have attested weaker effects in L2 processing (e.g., Kim & Grüter, 2021;Schlenter & Felser, 2021).…”
Section: Quantitative Differencesmentioning
confidence: 85%
“…In the following eye-tracking study to be discussed, time course differences were found to be coupled with less certainty in L2 processing. Mitsugi (2018) tested the use of numeral classifiers in Japanese to predict the upcoming noun. Nouns in Japanese fall into different classes and, when quantified, are preceded by a classifier associated with that class.…”
Section: Quantitative Differencesmentioning
confidence: 99%